Nutrition and anxiety disorders - Musa, Ramli (Springer, 2022)
Food and anxiety are interrelated to each other in various relationships. Food may worsen the anxiety symptoms; hence, modification of food intake would certainly help in alleviating some of the anxiety symptoms at a certain degree. Certain foods, particularly organic in nature, are also effective in helping the patients to go through the treatment course and fasten the recovery process. It may not be the only key solution or main treatment, but modification in dietary intake would help the sufferers. In this chapter, we outline how anxiety and types of food are interrelated and different types of food could help or worsen the anxiety symptoms. Also, at the end of this chapter, we outline the effects of microbiome on human guts and anxiety symptoms.